Story of Islam the coming of the Prophet [videorecording] - Dooley, John. ([S.l.] Polonius Production, 1991)
Summary: Traces the origin of the Islamic religion. Mohammad's life is chronicled and the history of Islam in relation to the Moslem people is outlined.
Keywords: Muhammad, Prophet -- d. 632; Prophets; Islam -- History; Islam -- Relations -- Christianity; Islam -- Relations -- Judaism; Muslims